Towards Broader Adoption of Educational Innovations in Undergraduate Water Resources Engineering: Views from Academia and Industry. (19th September 2018) - Habib, Emad; Deshotel, Matthew
Abstract: This article investigates the challenges that face the development, community‐scale adoption, and long‐term sustainability of educational innovations in the field of hydrology and water resources engineering undergraduate education. Adopting a customer‐based discovery process, the current study conducted a set of 78 informal interviews with two main groups: faculty members who teach water resources and hydrology courses, and practicing engineers with specialty in the same field. The interviews revealed that the main motivation for faculty to develop or adopt new educational innovations stems from self‐efficacy and desire to achieve effective instructional strategies. Other factors, such as institutional requirements and faculty evaluations and incentives, seem to play a modulating role for generating self‐created motivation. The results identified time limitations and steep learning‐curves as the two adoption hindering factors cited by a majority of the interviewees. Other hindering factors reported were rigidity of resources and lack of assessment data. Industry perspectives on preparedness of recent graduates and relation to current educational practices showed that young engineers may lack critical skills on the proper use and interpretation of data and modeling analyses. The study also discusses potential solutions, such as development of sharing environments to facilitate exchange of data and resources, modular design to support adaptation and compatibility with existing curricula, collaborative efforts to produce shareable evaluation and assessment data, and potential opportunities for collaboration between academia and the professional industry to facilitate development and sustainability of educational innovations.